Dui Lisu (Dui Menre yang dikembalikan) Menurut Perspektif Hukum Islam - Tarmizi Tarmizi (Jurnal Ilmiah Al-Tsarwah : ilmu ekonomi dan keuangan (konvensional dan syariah), 2018)
This paper discusses the "Dui Lisu (Dui Menre who is returned) according to the perspective of Islamic law" by revealing the following issues: (1) How to dui lisu with Bugis Traditional law, and (2) How to dui lisu with Islamic law. Dui lisu in view of Bugis custom law is dui menre returned by the women to the men, both returns are half or more. This is because the woman does not fulfill her duty as a wife. Whereas the law of dui lisu according to the Islamic law's view is prohibited. Asking dui lisu is tantamount to asking for a return which in Islamic law is prohibited